Fatal Bilateral Chylothorax in Mice Lacking the Integrin α9β1 - Huang, X. Z. (American Society for Microbiology, 2000)
Members of the integrin family of adhesion receptors mediate both cell-cell and cell-matrix interactions and have been shown to play vital roles in embryonic development, wound healing, metastasis, and other biological processes. The integrin α9β1 is a receptor for the extracellular matrix proteins osteopontin and tenacsin C and the cell surface immunoglobulin vascular cell adhesion molecule-1. This receptor is widely expressed in smooth muscle, hepatocytes, and some epithelia. To examine the in vivo function of α9β1, we have generated mice lacking expression of the α9 subunit. Mice homozygous for a null mutation in the α9 subunit gene appear normal at birth but develop respiratory failure and die between 6 and 12 days of age. The respiratory failure is caused by an accumulation of large volumes of pleural fluid which is rich in triglyceride, cholesterol, and lymphocytes. α9(−/−) mice also develop edema and lymphocytic infiltration in the chest wall that appears to originate around lymphatics. α9 protein is transiently expressed in the developing thoracic duct at embryonic day 14, but expression is rapidly lost during later stages of development. Our results suggest that the α9 integrin is required for the normal development of the lymphatic system, including the thoracic duct, and that α9 deficiency could be one cause of congenital chylothorax.